The secret of job success self-management skills - Holohan, Ellin; Jean Robbins (New York: Sunburst Communication, 1990)
The secret of job success indentities the behaviors the employers find unacceptable and then models the positive self-management skills that young people can use to meet employer expectations
Keywords: Management